Pengaruh pendidikan pelatihan dan kompetensi terhadap kinerja anggota satuan reskrim pada Polres Kota Metro Lampung - Ricky Fajar Adiputra; Marnis '; Errin Yani Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims at the analysis of the influence caused by educational training variables and variable performance against competencies.This study uses census techniques that take all the population numbers that add up to 51 people sample analysis method used in this research is quantitative descriptive method, analysis of partially and simultaneous (multiple linear analysis with the help of the program SPSS version 19.0)From the results of testing that has been carried out simultaneous regression test (test f) showed that the free variables examined have a significant influence on the variable performance. Partial regression test (test t) indicates that the variable factors of the training education have the most significant influence on the performance of variable magnitude influence posed (R) by the two free variables together-equal to variable terikatnya 70.5% while the rest of 29.5% is affected by other variables not examined in this study.Keywords: Education, Training, Competency and performance